The Role of Social Support and Life Satisfaction in Predicting Academic Burnout - zohreh sayadpour; fariborz Dortaj; Alireza Kiamanesh (پژوهش در نظام‌های آموزشی, 2021)
This study aimed to investigate the role of social support and life satisfaction in academic burnout. The research method was correlation. From Islamic Azad University of Tehran, 393 students selected by cluster sampling method and responded to Maslach Burnout Inventory-Student Survey (MBI-SS, Schaufeli et al., 2002), Satisfaction with Life Scale (SWLS, Diner et al., 1985) and Multidimensional Scale of Perceived Social Support (Zimet et al., 1988). Data were analyzed using regression analysis. The results showed that social support (β = -0.131, P≥0.020) and life satisfaction (β = -0.229, P≥0,000) had a significant and inverse effect on academic burnout. The findings also showed that Social support and life satisfaction explained 14% of the variance in academic burnout. According to the findings, academic burnout decreases with increasing social support and life satisfaction. Therefore, supporting student by family, friends, and the educational environment, as well as strategies that increase life satisfaction, can reduce students' academic burnout, which is an important factor in dropout.